Former charcoal kiln platforms as microhabitats affecting understorey vegetation in Mediterranean forests. Issue 3 (30th March 2016) - Carrari, Elisa; Ampoorter, Evy; Verheyen, Kris; Coppi, Andrea; Selvi, Federico
Abstract: Aim: Production of wood charcoal is an ancient form of anthropogenic forest use that existed for millennia in Mediterranean countries and only vanished in the last century. As a result, thousands of abandoned charcoal kiln platforms still occur in present‐day woodlands. Because of peculiar light and soil properties, the understorey vegetation at these platforms may differ from the surrounding stands. Our study investigated, for the first time, the effects of abandoned kiln platforms on understorey vegetation diversity, composition and biomass production in forests of a Mediterranean area. Location: Tuscany, central Italy. Methods: One 3 × 3 m kiln plot on charcoal kiln area and one 3 × 3 m control plot in the surrounding stands were established in 59 representative sites located in three major forest types dominated by evergreen sclerophylls, deciduous oaks and beech. In each plot, diversity and composition of the understorey community were analysed, together with soil factors (content of C, N, C:N ratio, pH) and light conditions (PAR). A 50 × 50 cm frame was randomly placed in each plot to measure biomass production. Results: The charcoal kiln habitat positively affected understorey diversity and above‐ground biomass, as well as the content of C, C:N ratio, pH and light availability. Significant compositional differences between the two plot types occurred, although to a variable extent for the three forest types. Graminoids were more abundant on kiln plots, and 12 indicator species were found for this habitat in deciduous oak forests. Higher values of cover and biomass showed the lack of detrimental effects of wood charcoal accumulation on understorey productivity. Conclusions: Long‐term wood charcoal production in Mediterranean woodlands has caused long‐lasting effects on the understorey via persistent changes in abiotic factors. Hence, former kiln platforms represent anthropogenic microhabitats that increase biodiversity and fine‐scale heterogeneity of forest ecosystems. Conservation measures are advocated to preserve them against various external threats. Abstract : The paper describes for the first time the legacy effects of abandoned charcoal kiln platforms on the understorey vegetation in Mediterranean woodlands. Due to altered soil and light conditions, understorey showed compositional differences and increased diversity and biomass. Such effects show that the old platforms represent persistent anthropogenic microhabitats enhancing fine‐scale heterogeneity and forest plant diversity. Conservation measures are suggested.